Use of sound therapy in management of tullio phenomenon associated with unilateral endolymphatic hydrops - Mustafa, Mohamed Wael M.; Abdelmaksoud, Aida A. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The tullio phenomenon consists of the production of vestibular signs or symptoms by an acoustic stimulus. TP was found to be present in many inner ear pathologies such as superior semicircular canal dehiscence, perilymphatic fistula and endolymphatic hydrops. No previous study probed the value of tinnitus maskers in the alleviation of Tullio phenomenon associated with endolymphatic hydrops. Methods: Twenty one patients who had a confirmed unilateral endolymphatic hydrops associated with Tullio phenomenon were selected for the study. Their age ranged from 20 to 52 years old. Tinnitus masker±amplification was used according to the audiological findings of each patient. The device was used in the affected ear for a minimum of 6 months. Results: Ten patients reported marked improvement on a graded scale with a mean of 8.6±1.2 as regards the occurrence of tullio phenomenon. Six patients achieved an average amelioration (mean 5.9±0.12) while five patients reported failure of the device (mean 3.4±0.6). Conclusions: Sound therapy using tinnitus masker±amplification is a good tool for alleviation of tullio phenomenon associated with unilateral endolymphatic hydrops.